ANALISIS SEMANTIK RAGAM BAHASA GAUL OLEH GEN ALPHA PADA APLIKASI TIKTOK MRCI.TV - Aziza Marwanti, Afina; Septian Dwi Hidayati, Devita; Zahara Ziza Yan, Hammassa; Hikam Arasy, Muhammad; Rafa Arianto, Naura; Valentina Febrianti, Nessa; Sholihatin, Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The slang used by Generation Alpha is influenced by the development of social media, technology, and information. Generation Alpha itself is a human being born from 2010 to 2025, which many people call the child of the Millennial Generation and also the younger sibling of Generation Z. The Tiktok platform is the main media that bridges language development. This research was conducted with the aim of (1) knowing the variety of Alpha Generation slang in the TikTok mrci.tv account, (2) knowing the connotation meaning of the Alpha Generation slang variety in the TikTok mrci.tv account, and (3) knowing the context of using the Alpha Generation slang variety in the TikTok mrci.tv account. The method used in making this scientific work is a qualitative method obtained through observation, listening, and recording. Generation Alpha has access to global information quickly and easily so that they absorb new vocabulary from various languages. The vocabulary is modified into slang that is adapted to their social context. The results revealed that (1) the varieties of Alpha Generation slang in the TikTok account mrci.tv are sigma, rizz, mewing, skibidi, ohio, big l, gyatt, blud, no cap, +1000 Aura, fannum tax, yapping. (2) the connotation meaning of the Alpha Generation slang variety in the TikTok mrci.tv account is that sigma means best, rizz means dazzling, mewing means cool, ohi means weird, and (3) the context of use of the Alpha Generation slang variety in the TikTok mrci.tv account is that it is used in non-formal situations and used in daily conversations with peers.